Identification of the symbiosis island of Bradyrhizobium paxllaeri LMTR 21T - Ormeño-Orrillo E. (2020)
The complete symbiosis island (SI) of Bradyrhizobium paxllaeri LMTR 21T, a mutualistic symbiont of the legume Phaseolus lunatus, was identified and analyzed. The SI was 646 kb in size, had lower G+C content than the genome average, and encoded not only nodulation and nitrogen fixation functions but also those for hydrogen uptake, vitamin and phytohormone biosynthesis, molybdenum transport, nonribosomal peptide synthesis, and type III secretion. Additionally, two divergent nodA genes were encoded in the SI. © 2019, Sociedade Brasileira de Microbiologia.